Abortion and Infanticide in the Modern Hungarian Criminal Law - Eva Repková (Societas et Iurisprudentia, 2014)
The deliberate killing of an unborn child – abortion and the intentional killing of newborns by their mothers – infanticide have always been a rather frequent phenomenon. Certain cultures tolerated these acts, but on the other hand, many civilizations severely punished them, which was related to the advancement of value orientation of the culture or to the established normative system. The protection of unborn and newborn children became the part of the Hungarian criminal law as the value of fundamental social importance, especially under the influence of Christian principles those considered child to be an absolute social value since the conception. Abortion and infanticide legislation fluctuated from relatively lenient canonical penalties and homage in the Middle Ages through the New Ages draconian absolutistic criminal codes, which almost regularly used a capital punishment for such offenses. The period of the 19th century represents a radical political and cultural break and could be considered a beginning of mitigating the criminal prosecution of these offenses, which means a transformation of the entire purpose of punishment, as well. The paper is therefore focused specifically on the period of the 19th century in order to provide an overview of the criminal legislation and judicial decisions in relation to these offenses. The study emphasizes the modifications to the legislation of abortion and infanticide which are simultaneously compared with absolutistic scribes of the Habsburg monarchy and modern criminal legislation.